2022
DOI: 10.3390/ijms23031024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Sulfide in Plant Roots during Development and in Response to Abiotic Stress

Abstract: Hydrogen sulfide (H2S) is regarded as a “New Warrior” for managing plant stress. It also plays an important role in plant growth and development. The regulation of root system architecture (RSA) by H2S has been widely recognized. Plants are dependent on the RSA to meet their water and nutritional requirements. They are also partially dependent on the RSA for adapting to environment change. Therefore, a good understanding of how H2S affects the RSA could lead to improvements in both crop function and resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…In another study, H2S application with a concentration of 0.4 mM NaHS elevated the progress of lateral roots in wheat. The number and length of lateral roots increased in number as well as their density (Li et al 2022). Li et al (2022) also reported that H2S application could improve root growth with its inhibitory effect on abiotic stress in many plants.…”
Section: H 2s Application Effects On Beans Under Salt Stressmentioning
confidence: 95%
See 2 more Smart Citations
“…In another study, H2S application with a concentration of 0.4 mM NaHS elevated the progress of lateral roots in wheat. The number and length of lateral roots increased in number as well as their density (Li et al 2022). Li et al (2022) also reported that H2S application could improve root growth with its inhibitory effect on abiotic stress in many plants.…”
Section: H 2s Application Effects On Beans Under Salt Stressmentioning
confidence: 95%
“…It is known that H2S alleviates the effect of stress in plants by increasing photosynthetic activity in saline conditions, changing antioxidant enzyme activity to increase stress tolerance, and modulating signal-transmission pathways (Ding et al 2019). Hydrogen sulfide is also effective in increasing plant resistance to environmental stress factors through the development of antioxidant systems in case of osmotic stress, hypoxia, and temperature stress (Li et al 2016(Li et al , 2022da-Silva and Modolo 2018). Previous studies showed that H2S at low concentrations is crucial in the plant life cycle, from germination to growth as well as against environmental stress responses ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies identified mechanisms involving genes, proteins, and metabolites that underlie plant responses to stress conditions (Chen et al, 2022;Hassan et al, 2022;Huang et al, 2022;Mittler et al, 2022;Yang et al, 2022;Zhan et al, 2022). Some of these molecules were used to improve plant responses to abiotic and biotic stresses (Li et al, 2022;Mahto et al, 2022;Wang and Komatsu, 2022;Zhao et al, 2022). However, the underlying structural and functional relationships of these molecular mechanisms require more research.…”
Section: Editorial On the Research Topic Structural Bioinformatics An...mentioning
confidence: 99%
“…They found that increases in the expression of chlorophyll degradation genes NYC1 , PAO , PPH , SGR1 , and senescence-associated genes ( SAGs ) during senescence were attenuated by LCD1 overexpression, whereas lcd1 mutants showed enhanced senescence-related parameters. In the review of Li et al, the regulation of H 2 S on the root system architecture (RSA) was summarized in terms of primary root growth, lateral and adventitious root formation, root hair development, and the formation of nodules [ 16 ]. The genes involved in the regulation of the RSA by H 2 S, and the relationships with other signal pathways were also discussed.…”
mentioning
confidence: 99%